756 The Effectiveness of RDW-CV in Differentiating Microcytic Anemia. (October 2012) - Neamtu, ML; Dobrota, L; Neamtu, MB; Diac, FS; Simina, II
Abstract : Backround: Iron deficiency anemia (IDA) and thalassemia are the most common microcytic anemia in children. Sometimes, expensive or invasive investigations are necessary for their distinction. Red cell distribution - coefficient variation (RDW-CV) is a new generation marker more often used in differentiating IDA from thalassemia. A number of hematological indices are also useful (Mentzer, Shine&Lal, Green&King, Ricerca). Aim: To demonstrate the effectiveness RDW - CV in differentiating microcytic anemia. Method: Retrospective study conducted on a total of 215 patients with microcytic anemia. Criteria for study group selection: MCV and Hb below the minimum age reference (mild anemia, Hb between 9–11 g/dl and moderate anemia from 8.5–9 g/dl), without a history of other hematologic disorders or chronic diseases. Sideremia was determined to all patients to confirm the diagnosis of IDA (the least expensive investigation for distinction). The RDW - CV > 16% was considered pathological. Results: 98 patients had low levels of sideremia, 134 patients had mild anemia and 81 - moderate anemia. RDW-CV was significantly correlated with sideremia, strongly for the group with mild anemia (p<0.05). Statistical significance was observed for Shine&Lal (p<0.006), Green & King (p<0.005), Ricerca (p<0.05). The greatest sensitivity presented Green&King (72%), followed by Shine&Lal and Ricerca, and the highest specificity Shine&Lal and Ricerca (92%). Conclusions: RDW-CV is useful in differentiating IDA, especially in mild forms. Although Green&King index is the most sensitive, we support Ricerca index for simple calculation formula.